Apakah CG Disclosure dan ROE Mempengaruhi Financial Distress? - Risnafitri, Hafizhah; Amri, Abrar; Hidayat, Rahmat; Albet, Albet; Soufyan, Dara Angreka (Universitas Teuku Umar, 2025)
Financial Distress (FD) is a critical stage requiring an accurate early warning system. Previous studies identify profitability (Return on Equity - ROE) and Corporate Governance (CG) as key determinants. However, gaps exist regarding CG's weakening effectiveness under pressure and the challenging interpretation of high profitability in the Indonesian context. This study aims to examine the effect of the Corporate Governance Disclosure Index (CGDI) and ROE on FD probability. The methodology employs Logistic Regression on 256 companies from the Cyclical Industry (2023–2024). Variables and measures utilized include: FD as the binary dependent variable (Springate S-Score), CGDI and ROE as an independent. The model was found to be simultaneously significant in predicting FD, yet the Hosmer and Lemeshow Test indicated the model is not fully fitted. Individually, CGDI has no significant effect on FD. This finding supports the view that formal CG mechanisms lose monitoring effectiveness under financial pressure (distress), often acting as mere formal legitimacy (Legitimacy Theory). Conversely, ROE has a significant and positive effect on FD probability. This counter-intuitive finding is interpreted as illusory profitability or earnings management due to strong managerial incentives (Agency Theory). High ROE becomes a misleading signal, reinforcing that profitability interpretation is a major issue within the Indonesian distress context. Consequently, the findings highlight the imperative for market participants to shift analytical focus toward underlying cash flow and liquidity indicators, while demonstrating the need for internal CG mechanisms beyond mere disclosure to effectively mitigate financial distress risk in the Indonesian market environment.